PEMANFAATAN SOFTWARE MICROSOFT MATHEMATICS DALAM PEMBELAJARAN MATRIKS - Rahayuningsih, Suesthi (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2018)
Matrix is ​​a sub subject of mathematics that must be mastered by students. The matrix generally involves numbers or algebra arranged in certain entries (located on rows and columns of ke-). In solving the problem of matrix operation is not really difficult to solve, just to operate the matrix there are some other concepts to be understood. However, on the ground fact that there are still many students who have not mastered this sub-material, due to lack of understanding of students about the concept used to operate the matrix. As an alternative to overcome it then introduced the use of Microsoft Mathematics software in teaching and learning process on learning matrix. Thus expected to provide motivation to study matrix in a way that is not boring that can ultimately improve student learning outcomes of the material. This research is only limited to theoretical studies and not yet implemented.